Two-dimensional metal–organic framework Mo3(C2O)12 as a promising single-atom catalyst for selective nitrogen-to-ammonia conversion. Issue 9 (7th February 2022) - Feng, Zhen; Yang, Zelin; Meng, Xiaowen; Li, Fachuang; Guo, Zhanyong; Zheng, Shu; Su, Guang; Ma, Yaqiang; Tang, Yanan; Dai, Xianqi
Abstract : 2D MOF Mo3 (C2 O)12 not only possesses sufficient stability, but also exhibits high NRR activity with a low limiting potential of −0.36 V and substantial selectivity with a promising theoretical faradaic efficiency value of 100%. Abstract : The development of single-atom catalysts (SACs) for the electrocatalytic nitrogen reduction reaction (NRR) remains a great challenge. Using density functional theory calculations, we design a new family of two-dimensional metal–organic frameworks [TM3 (C2 O)12, TM = Sc–Au] and explore their feasibility as SACs for the NRR. The calculated adsorption Gibbs free energies of N2 and NNH species demonstrate that only the Mo3 (C2 O)12 monolayer could both activate the NN bond and stabilize the adsorbed NNH intermediate. The Mo3 (C2 O)12 metal–organic framework not only possesses sufficient stability, but also exhibits high nitrogen fixation activity and substantial selectivity. The NRR distal pathway could achieve this sufficient goal with a low limiting potential of −0.36 V and a promising theoretical faradaic efficiency value of 100%. This work could give guidance to develop more effective NRR SACs using 2D metal–organic frameworks under ambient conditions.